2022
DOI: 10.1007/s40257-022-00739-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Roflumilast Cream (ARQ-151) on Itch and Itch-Related Sleep Loss in Adults with Chronic Plaque Psoriasis: Patient-Reported Itch Outcomes of a Phase 2b Trial

Abstract: Background Itch is the most bothersome symptom reported by patients with psoriasis. Safe and effective treatments for psoriasis that also address itch are needed. Objectives To report effects of roflumilast cream on itch-related outcomes from a Phase 2b trial. Methods Adults with chronic plaque psoriasis were randomized to roflumilast 0.3%, roflumilast 0.15%, or vehicle once-daily for 12 weeks. Psoriasis severity was assessed via the Investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Post hoc analysis of the phase 2b study found significant improvements in itch (as measured by the worst itch numeric rating scale, WI-NRS) and in itch-related sleep loss, with WI-NRS improvement occurring as early as week 2 in the roflumilast groups, and improvement in itch-related sleep loss from week 6 onward in both roflumilast groups [32 ▪ ].…”
Section: Phosphodiesterase-4 Inhibitionmentioning
confidence: 96%
See 1 more Smart Citation
“…Post hoc analysis of the phase 2b study found significant improvements in itch (as measured by the worst itch numeric rating scale, WI-NRS) and in itch-related sleep loss, with WI-NRS improvement occurring as early as week 2 in the roflumilast groups, and improvement in itch-related sleep loss from week 6 onward in both roflumilast groups [32 ▪ ].…”
Section: Phosphodiesterase-4 Inhibitionmentioning
confidence: 96%
“…Post hoc analysis of the phase 2b study found significant improvements in itch (as measured by the worst itch numeric rating scale, WI-NRS) and in itchrelated sleep loss, with WI-NRS improvement occurring as early as week 2 in the roflumilast groups, and improvement in itch-related sleep loss from week 6 onward in both roflumilast groups [32 ]. The DERMIS-1 and DERMIS-2 phase 3 trials each randomized participants over 2 years old with plaque psoriasis affecting from 2 to 20% BSA to receive roflumilast 0.3% or placebo in a 2 : 1 ratio.…”
Section: Phosphodiesterase-4 Inhibitionmentioning
confidence: 97%
“…39 Analyzing the effects of roflumilast cream on itchrelated outcomes on patients from the same trial, the authors found that roflumilast cream improved itch and itch-related sleep loss associated with chronic plaque psoriasis compared with vehicle, at 2 weeks of treatment. 41 A post hoc analyses of the same study data on 160 (48% of 331 patients randomized to roflumilast 0.3%, roflumilast 0.15%, or vehicle) with psoriasis involving the face and/or intertriginous areas found that the rates of adverse events were low in all treatment groups, similar to the overall population. Based on the author statements in a Research letter published in British Journal of Dermatology, 42 their results suggest that patients with plaque psoriasis on the face and/or intertriginous regions, which is frequently challenging to treat due to the sensitivity of these regions, may benefit from topical roflumilast 0.3%.…”
Section: Clinical Trialsmentioning
confidence: 97%
“…Roflumilast cream was FDA approved for plaque psoriasis in July 2022, as it rapidly and effectively reduced itch severity, providing improvement after 2 weeks with a reduction in worst itch of − 4 on a 10-point scale at week 8 [ 16 , 17 ]. Furthermore, in two pivotal phase III trials, DERMIS-1 and DERMIS-2, 67.5% and 69.4% of patients treated with roflumilast and with baseline WI-NRS scores ≥ 4 had at least a 4-point reduction in score (WI-NRS Success) compared to 26.8% and 35.6% of patients treated with vehicle cream, respectively [ 18 ].…”
Section: Phosphodiesterase 4 Inhibitors (Roflumilast Difamilast Lotam...mentioning
confidence: 99%